2007
DOI: 10.1088/0026-1394/44/6/n02
|View full text |Cite
|
Sign up to set email alerts
|

Re-evaluation of the BIPM international standard for air kerma in60Co gamma radiation

Abstract: A re-evaluation of the BIPM standard for air kerma in 60 Co radiation has been made. The changes to the air-kerma rate determination arise from four sources: (i) the results of Monte Carlo calculations of correction factors for the standard; (ii) a re-evaluation of the correction factor for saturation; (iii) a new evaluation of the air volume of the standard using an experimental chamber of variable volume; (iv) the adoption of a new reference beam at the BIPM. The combined effect of these changes is an incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 4 publications
1
38
0
Order By: Relevance
“…37 stopping powers are used to evaluate the graphite/air stopping-power ratio. This W / e value is consistent with the second value determined by Niatel et al if one takes into account the recent changes in the BIPM standard for air kerma ͑exposure͒, 14 and is consistent also with the experimental results of Büermann et al 25 based on the comparison of the ionometric measurements and calorimetric measurements. If the extreme value of 86.8 eV for the mean excitation energy for graphite is used to evaluate the graphite stopping power, then the value obtained for W / e is 34.15Ϯ 0.23% J / C. Direct measurements of W / e values 2 for low-energy electrons have shown that W / e values approach a constant value very close to 34 J / C. It is reasonable to believe that the value of W / e remains constant for higher energies, this suggests that a higher I value may be more appropriate than that used in ICRU Report No.…”
Section: Discussionsupporting
confidence: 91%
“…37 stopping powers are used to evaluate the graphite/air stopping-power ratio. This W / e value is consistent with the second value determined by Niatel et al if one takes into account the recent changes in the BIPM standard for air kerma ͑exposure͒, 14 and is consistent also with the experimental results of Büermann et al 25 based on the comparison of the ionometric measurements and calorimetric measurements. If the extreme value of 86.8 eV for the mean excitation energy for graphite is used to evaluate the graphite stopping power, then the value obtained for W / e is 34.15Ϯ 0.23% J / C. Direct measurements of W / e values 2 for low-energy electrons have shown that W / e values approach a constant value very close to 34 J / C. It is reasonable to believe that the value of W / e remains constant for higher energies, this suggests that a higher I value may be more appropriate than that used in ICRU Report No.…”
Section: Discussionsupporting
confidence: 91%
“…The standards CSp03 and Sp03 were used for the present comparison, but they were considered as transfer 2/13 chambers rather than primary standards. The BIPM primary standard is a parallel-plate graphite cavity ionization chamber with a volume of about 6.8 cm 3 as described in [5] and [6]. is the average energy spent by an electron of charge e to produce an ion pair in dry air, g is the fraction of electron energy lost by bremsstrahlung production in air, ( en /) a,c is the ratio of the mean mass energy-absorption coefficients of air and graphite, s c,a is the ratio of the mean stopping powers of graphite and air,  k i is the product of the correction factors to be applied to the standard.…”
Section: Details Of the Standardsmentioning
confidence: 99%
“…--I ionization current / pA ---0.01 0.02 (5) --Relative standard uncertainty quadratic summation 0.02 0.15 0.08 (6) 0.31 combined uncertainty 0.15 0.32 (1) Expressed as one standard deviation s i represents the type A relative standard uncertainty estimated by statistical methods, u i represents the type B relative standard uncertainty estimated by other means (2) At 101 325 Pa and 273.15 K for the BIPM; at 101 325 Pa and 293.15 K for the LNHB (3) Combined uncertainty for the product of a c s , and e W / (4) The uncertainties for k wall and k an are included in the determination of the effective volume [6] (5) The reference air-kerma rate is derived from the six values for (I k s k st k wall k an k rn k pol ) /V determined for the six ionization chambers. Values for each chamber are given in [4] (6) A global type A uncertainty of 8 parts in 10 4 is determined from the spread of the six values for (I k s k st k wall k an k rn k pol ) /V…”
Section: Physical Data and Correction Factorsmentioning
confidence: 99%
See 2 more Smart Citations